2020
DOI: 10.3390/cancers12040781
|View full text |Cite
|
Sign up to set email alerts
|

Radiopharmaceuticals for Breast Cancer and Neuroendocrine Tumors: Two Examples of How Tissue Characterization May Influence the Choice of Therapy

Abstract: Molecular medicine has gained clinical relevance for the detection and staging of oncological diseases, to guide therapy decision making and for therapy follow-up due to the availability of new highly sensitive hybrid imaging camera systems and the development of new tailored radiopharmaceuticals that target specific molecules. The knowledge of the expression of different receptors on the primary tumor and on metastases is important for both therapeutic and prognostic purposes and several approaches are availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…This technique is non-invasive, reproducible and provides valuable information of the tumor stage. In addition, [ 18 F]-FES uptake is correlated with ER overexpression, such correlation can predict the patient's response to hormonal therapy (HT) [186]. [ 18 F]-FES PET as a diagnostic tool can differ from early stage tumors and metastases, this modality is usually used instead of biopsy or when it has undetermined results [186][187][188]).…”
Section: Future Role Of Positron Emission Tomography and New Tracersmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is non-invasive, reproducible and provides valuable information of the tumor stage. In addition, [ 18 F]-FES uptake is correlated with ER overexpression, such correlation can predict the patient's response to hormonal therapy (HT) [186]. [ 18 F]-FES PET as a diagnostic tool can differ from early stage tumors and metastases, this modality is usually used instead of biopsy or when it has undetermined results [186][187][188]).…”
Section: Future Role Of Positron Emission Tomography and New Tracersmentioning
confidence: 99%
“…In addition, [ 18 F]-FES uptake is correlated with ER overexpression, such correlation can predict the patient's response to hormonal therapy (HT) [186]. [ 18 F]-FES PET as a diagnostic tool can differ from early stage tumors and metastases, this modality is usually used instead of biopsy or when it has undetermined results [186][187][188]). A study carried by van Kruchten et al in 33 patients who underwent [ 18 F]-FES PET reported [ 18 F]-FES positive lesions in 22 patients, higher bone metastases lesions were detected by [ 18 F]-FES PET compared with other conventional imaging methods (341 vs 246 bone metastases lesions respectively), additionally, an 88% improvement in diagnosis and 48% of the patients reported a change in therapy [186,188].…”
Section: Future Role Of Positron Emission Tomography and New Tracersmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that this therapeutic protocol imposes patient high costs and despite that may be ineffective, assessment pre-treatment physiologic manner of the trastuzumab would be noteworthy. Also, this is demonstrated that some negative HER2 patients can benefit from therapeutic trastuzumab as an anti-HER2 agent [ 48 ]. In this regard biodistribution and accumulation of trastuzumab radiolabelled with Indium-111, [ 111 In]In-trastuzumab, as an imaging agent for single photon computed emission tomography (SPECT) has been evaluated [ 48 ].…”
Section: Targeting Her2 Receptors By Theranosticsmentioning
confidence: 99%
“…Also, this is demonstrated that some negative HER2 patients can benefit from therapeutic trastuzumab as an anti-HER2 agent [ 48 ]. In this regard biodistribution and accumulation of trastuzumab radiolabelled with Indium-111, [ 111 In]In-trastuzumab, as an imaging agent for single photon computed emission tomography (SPECT) has been evaluated [ 48 ]. In preclinical studies, significant and specific accumulation of [ 111 In]In-trastuzumab was proved in human HER2 tumour-bearing mice [ 49 ].…”
Section: Targeting Her2 Receptors By Theranosticsmentioning
confidence: 99%